2009
DOI: 10.2215/cjn.03980808
|View full text |Cite
|
Sign up to set email alerts
|

Association of Markers of Iron Stores with Outcomes in Patients with Nondialysis-Dependent Chronic Kidney Disease

Abstract: Background and objectives: Assessments of iron stores by serum iron saturation ratio (ISAT) and ferritin are used to direct anemia therapy in chronic kidney disease (CKD) and are associated with clinical outcomes in patients on dialysis. The association of ISAT and ferritin with outcomes in patients with nondialysis-dependent CKD (NDD-CKD) has not been studied.Design, setting, participants, & measurements: All-cause mortality and progression of CKD [slopes of estimated GFR (eGFR)] were examined in 453 men with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…A study examining predialysis CKD patients has revealed that high TSAT is associated with a decrease in GFR and that the mortality rate tends to increase in patients with advanced CKD with serum ferritin levels ≥250 ng/mL [140].…”
Section: Statement 3-2 *mentioning
confidence: 99%
“…A study examining predialysis CKD patients has revealed that high TSAT is associated with a decrease in GFR and that the mortality rate tends to increase in patients with advanced CKD with serum ferritin levels ≥250 ng/mL [140].…”
Section: Statement 3-2 *mentioning
confidence: 99%
“…Even in the absence of anemia, iron deficiency is a potent substrate for dyspnea and exercise intolerance (26,27) and identifies those in the general population at a heightened risk for mortality (28). In patients with uremia, lower levels of transferrin saturation (TSAT), a more reliable marker of iron deprivation than ferritin in inflammatory cohorts, also correlate to poorer survival (29). Whether lower TSAT relates to mortality independently and more powerfully than anemia in CHF remains unclear.…”
Section: See Page 1252mentioning
confidence: 99%
“…Recently, in CKD patients not on dialysis, it was found that the lower the %Tf Sat the higher the mortality, again raising the possibility that iron deficiency may be a common and reversible cause of severe cardiovascular disease [63]. Although there has been concern about increased iron stores being associated with increased risk of coronary heart disease [64], this has not been confirmed by some recent studies [65] and the issue is still controversial.…”
Section: The Effect Of IV Iron Alone In the Anemia Of Chfmentioning
confidence: 99%